2019
DOI: 10.3390/rs11131562
|View full text |Cite
|
Sign up to set email alerts
|

Crack Propagation and Fracture Process Zone (FPZ) of Wood in the Longitudinal Direction Determined Using Digital Image Correlation (DIC) Technique

Abstract: As a state-of-the-art method, the digital image correlation (DIC) technique is used to capture the fracture properties of wood along the longitudinal direction, such as the crack propagation, the strain field, and the fracture process zone (FPZ). Single-edge notched (SEN) specimens made of Douglas fir (Pseudotsuga menziesii) from Canada with different notch-to-depth ratios are tested by three-point-bending (3-p-b) experiment. The crack mouth opening displacements (CMOD) measured by the clip gauge and DIC techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Studies have shown that as the number of cracks increase, the values of MOE noticeably decrease. This observation confirms the results of previous research conducted by Schajer et al [ 26 ], Olsson et al [ 58 , 61 ], Burchelt et al [ 17 ], and Yu et al [ 62 ] concerning the effect of the presence of cracks on the timber strength index determined using the modulus of elasticity. The Spearman’s rank correlation coefficient for wide planes labeled as 0 and 1 had slightly negative values of R = −0.342 and R = −0.356, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Studies have shown that as the number of cracks increase, the values of MOE noticeably decrease. This observation confirms the results of previous research conducted by Schajer et al [ 26 ], Olsson et al [ 58 , 61 ], Burchelt et al [ 17 ], and Yu et al [ 62 ] concerning the effect of the presence of cracks on the timber strength index determined using the modulus of elasticity. The Spearman’s rank correlation coefficient for wide planes labeled as 0 and 1 had slightly negative values of R = −0.342 and R = −0.356, respectively.…”
Section: Resultssupporting
confidence: 92%
“…These features manifest themselves at the post-peak stage of deformation due to the growth of plastic strains and, as a consequence, the appearance of an almost horizontal section on the load-displacement curve. For example, for cubic spruce specimens of 40 × 40 × 40 mm (humidity 18%) under compression along the fibers with a controlled displacement of 10 mm/min (Figure 1), experimental curves (Figure 2) were obtained (in the laboratory of the Institute of Forestry, Mining and Construction Sciences, Petrozavodsk State University), which are similar to other experimental curves of comparable tests known from the literature [30,[38][39][40]. We will analyze the behavior of wood under uniaxial compression using the plots in Figure 2 and the results of acoustic emission measurements in comparable tests known from the literature [30,33].…”
Section: Load-displacement Curve In Compression Tests Of Wood Along T...supporting
confidence: 78%
“…Tracking-based methods DIC: Bhattacharjee and Deb, 85 Yu et al 86 DIC-EFG: Zhu et al 87 Keypoint tracking using optical flow: Yin et al, 88 Kong and Li 89 Full field optical flow: Yang et al 90…”
Section: Crack Propagation Monitoringmentioning
confidence: 99%
“…During load test, the crack changes can also be monitored by using their approaches. Yu et al 86 monitored the crack propagation and fracture process zone of wood structures by using DIC to measure the crack mouth opening displacements. Zhu et al 87 integrated DIC and Element-free Galerkin (EFG) technique to evaluate the full field strain including the crack tip and calculate the stress intensity factor.…”
Section: Cv-shm-llmentioning
confidence: 99%